Development of An Android Application for Carpooling in UTHM - Law , Micheal Mao Sheng; Yasak, Zurina (Research and Innovation in Technical and Vocational Education and Training, 2021)
Carpooling is a transportation concept where the driver can share their vehicle with the passenger who need the ride. Excessive amount of vehicle is one of the main causes of air pollution and traffic jams, while the situation can totally be solved through carpooling. The problem is that there is no such a platform for people to carry out carpooling as well as to discuss about the details about the ride. Thus, ShareShare, an Android based application with the main objective to carry out carpooling is proposed. ShareShare is being developed according to the prototyping model, which used interviews as research instruments. ShareShare is developed based on Android device and Firebase is used as its database. ShareShare serves as a platform that allow users to provide or to request the carpooling services. Besides that, ShareShare also allow users to discuss about their trip or ride using the chat function provided. ShareShare is provided with emergency contact function to make sure the safety of every users when there are any emergency cases. After the evaluation from four persons of expert, ShareShare is getting a positive review and feedback in the interface design, the interactive design, and the overall satisfaction after using the application ShareShare. On the other hand, ShareShare do receive some useful advices from the experts to achieve a better improvement in the developed application, which included to consider the font size of the application to make sure it fits every type of devices